Period functions for C⁰- and C¹-flows - Maksymenko, S.I. (Український математичний журнал, 2010)
Let F:M×R→M be a continuous flow on a manifold M, let V ⊂ M be an open subset, and let ξ:V→R be a continuous function. We say that ξ is a period function if F(x, ξ(x)) = x for all x ∈ V. Recently, for any open connected subset V ⊂ M; the author has described the structure of the set P(V) of all period functions on V. Assume that F is topologically conjugate to some C1-flow. It is shown in this paper that, in this case, the period functions of F satisfy some additional conditions that, generally speaking, are not satisfied for general continuous flows. Нехай F:M×R→M — неперервний потік на многовиді M, V⊂M — відкрита підмножина ξ:V→R - неперервна функція. Назвемо ξ функцією періодів, якщо F(x,ξ(x))=x для всіх x∈V. Нещодавно для кожної відкритої зв'язної множини V⊂M автором було описано структуру множини P(V) всіх функцій періодів на V. Припустимо, що F є топологічно спряженим до деякого потоку класу C1. У даній роботі показано, що тоді функції періоду F задовольняють додаткові умови, які, взагалі кажучи, не виконуються для загальних неперервних потоків.